2018
DOI: 10.3121/cmr.2018.1385
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Chlorhexidine as a Disinfectant in Cleft Palate Surgery

Abstract: Objectives:Chlorhexidine is seen as the golden standard of disinfectants. It is widely used to clean surgical sites; however, many studies indicate resistance of pathogens to chlorhexidine. One study indicated that pathogenic microorganisms were isolated from the soft palate cleft region in 57% of patients with facial clefts. The objectives of our study were to determine (1) if chlorhexidine application is effective in removing pathogens from the surgical site in these patients, and (2) if any pathogens are is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…Nonetheless, only chlorhexidine, to our knowledge, has been tested in the cleft population. One study found a reduction in intraoral flora by approximately 50% following surgical site preparation of the palate with chlorhexidine (Roode and Butow, 2018). In this study, S aureus growth persisted in approximately 90% of cases.…”
Section: Surgical Site Preparationsupporting
confidence: 47%
See 1 more Smart Citation
“…Nonetheless, only chlorhexidine, to our knowledge, has been tested in the cleft population. One study found a reduction in intraoral flora by approximately 50% following surgical site preparation of the palate with chlorhexidine (Roode and Butow, 2018). In this study, S aureus growth persisted in approximately 90% of cases.…”
Section: Surgical Site Preparationsupporting
confidence: 47%
“…This is supported by studies suggesting that there are anatomical site-specific colonization rates in cleft patients (Cocco et al, 2010), that closure of the cleft reduces oral pathogen burden (Arief et al, 2005;Cocco et al, 2010), and that the size of fistulae directly correlates with pathogen transmission (Tuna et al, 2008). Furthermore, the rate of antibiotic resistance among commonly encountered oral bacteria in cleft patients appears high (Myburgh and Butow, 2009;Roode et al, 2017;Roode and Butow, 2018).…”
Section: Cleft Oral Floramentioning
confidence: 83%
“…55 As an anti-plaque agent, CHX is considered the gold standard by some authors. 55,56 Despite the benefits described above, prolonged use of CHX may cause several adverse effects such as: extrinsic staining of teeth, restorations, prostheses or tongue, 57 as well as taste alterations, reversible angioedema or swelling of the parotid glands, and desquamation of the oral mucosa. 58 There is evidence that the 0.2% CHX mouthwash provides a significantly greater reduction of plaque than 0.12% and 0.06% concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have examined the micro‐flora in facial clefts in infants and toddlers with seven of these identifying micro‐organisms preoperatively (Arief et al, 2005; Bokhout et al, 1996; Chuo & Timmons, 2005; Cocco et al, 2010; Myburgh & Bütow, 2009; Roode & Bütow, 2018; Roode et al, 2016). A study that aimed to identify possible pathogenic organisms associated with postoperative wound complications cultured 15 different pathogenic organisms preoperatively from 100 babies (Myburgh & Bütow, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…All these are pathogens that can contribute to postoperative infections. Another study on the resistance of pathogens against chlorhexidine in patients with preoperative cleft soft palate isolated 28 different pathogenic micro‐organisms from 50 patients (Roode & Bütow, 2018).…”
Section: Introductionmentioning
confidence: 99%